Malaysia-Singapore relations under Mohd Najib Tun Razak - Omar, Rusdi (2011)
Malaysia and Singapore enjoy and share a special relationship due to their geographical, historical, familial, cultural, political, economic and strategic features. Their relationship is characterized by interdependence.The competitive world has brought about a close neighborly cooperation between the two nations to build resilience and strength.This article will examine the state of bilateral relations between these two countries under Malaysia's Prime Minister Mohd. Najib, and will analyze the future prospect of Malaysia and Singapore under his era.Under his era, Malaysia has been embarking on a series of initiatives in improving her relationship with Singapore, leaving tensions that took place during Mahathir era. Looking at the history of relations between the two countries, the role of leadership has played important role in the up and down of relationship.Under new generation of leaders in these two countries, we expect that they have new visions and put more efforts to nurture good relations. Personal contacts involving leaders and government officials of both countries still become the bases of relations between these two closed neighbors.The understanding reached by the leaders of the two countries has been and remain the fundamental to preserving long term mutual benefits.Leaders of both countries can play significant roles in overcoming conflicts and finding solutions to the problems that besieged the relations between the two countries.If both countries could maintain the momentum and capitalize the benefits of these initiatives, we foresee that both countries will not enter into troubled relationships like the previous periods, but it augurs well for strengthened relationships in the future.